Peer abuse: Psychological and psychiatric aspects - Stanimirović Ljiljana (Association of Nurses Technicians and Midwives, 2019)
Domestic violence is defined as any form once committed or repeated verbal or nonverbal conduct that has the effect of an actual or potential threat to the health, development and dignity of children -students. Peer abuse is a form of aggressive behavior among children and youth of the same or similar age, and it is manifested in various ways and can permanently leave its consequences.According to the type, violence is divided into: physical, emotionaly-psychological, social, sexual, economic, information and informational violence. The causes of violent behavior are numerous and increasingly frequent subjects of research by psychologists, but the family and family relationships are set up as the pivot point. Child psychology claims that the development and upbringing of children are mutually dependent. Primary emotions, anger, fear, joy, sadness are the first to differentiate in the children of all cultures, they maintain during their entire life and condition temper, as one of the basic lines of personality, and make the disposition for emotional response during life. Neglecting children at an early age creates the possibility of dominant development of negative emotions. Emotions are an integral part of all complex dynamic personality dispositions, and emotional reactions are the psychic processes we use to evaluate known.Since peer abuse occurs during the period of development and defining of child's personality, the consequences can causea loss of the basic elements of personal identity, attitude towards others with a sense of guilt.Psychological consequences are invisible, but they can occur in terms of real mental illness, with a disorder of affectivity and depression that can end with suicide. The problem is very alarming and requires the engagement of the entire society, all institutions, at all levels, in all possible ways, to return the moral norms and principles of the family, with an appeal for more quality communication in the family and in the education of children.